2020
DOI: 10.26656/fr.2017.4(3).378
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of anthocyanin and ternatin flavonoids for the treatment of inflammation-related diseases using molecular docking analysis

Abstract: Inflammatory markers such as cyclooxygenase (COX)-2, inducible nitric oxide synthase (iNOS), myeloperoxidase (MPO), and prostaglandin (PEG) are widely known as major targets in discovering natural anti-inflammatory drugs for the treatment of inflammationrelated diseases. Non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen and aspirin are mostly used at present, however, some NSAIDS have been reported to cause gastrointestinal side effect due to ligand-protein interaction. Molecular docking is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…NSAIDs like sodium diclofenac and ibuprofen have shown interaction with iNOS with binding energy (ΔG) of about − 6.7kcal/mol and − 7.50kcal/mol respectively [53,54]. Also, it has been reported that diclofenac binds to Ser530 and Tyr385 residues of COX-2 active site [55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs like sodium diclofenac and ibuprofen have shown interaction with iNOS with binding energy (ΔG) of about − 6.7kcal/mol and − 7.50kcal/mol respectively [53,54]. Also, it has been reported that diclofenac binds to Ser530 and Tyr385 residues of COX-2 active site [55].…”
Section: Resultsmentioning
confidence: 99%
“…Our study has shown lower binding energy (ΔG= -9.46kcal/mol) between garcinol and iNOS rendering it a potent inhibitor. Several studies have reported many natural inhibitory ligands for iNOS and COX-2 by molecular docking analysis [51,54,[56][57][58][59]. It is well established that non-steroidal anti-in ammatory drugs (NSAIDS) operate by suppressing the release of prostaglandins by inhibiting COX-2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that anti-inflammatory drugs (NSAIDs) such as dexamethasone and indomethacin inhibit iNOS and COX-2 [5,81]. NSAIDs like sodium diclofenac and ibuprofen have shown interaction with iNOS with binding energy (ΔG) of about -6.7 kcal/mol and -7.50 kcal/mol, respectively [82,83]. Also, it has been reported that diclofenac binds to Ser530 and Tyr385 residues of the COX-2 active site [84].…”
Section: Discussionmentioning
confidence: 99%